Eight channels digital storage oscilloscope - Kandasamy, Amirthavel (2016)
The traditional two or four channels oscilloscope is not very useful to study behavior of many modern intelligent sensors or system on chips (soc) as many of them contains more than four signals. an eight channels digital storage oscilloscope is considered good to analyze these devices, hence, proposed in this project. this project is to demonstrate knowledge of microprocessor system design, skills in signal conditioning techniques and analogue system design involving op-amp by developing a prototype of eight channels digital storage oscilloscope.